2013
DOI: 10.1111/cas.12207
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated radiation‐induced nitric oxide promotes expansion of glioma stem‐like cells

Abstract: Glioblastoma remains an incurable brain disease due to the prevalence of its recurrence. Considerable evidence suggests that glioma stem-like cells are responsible for glioma relapse after treatment, which commonly involves ionizing radiation. Here, we found that fractionated ionizing radiation (2 Gy ⁄ day for 3 days) induced glioma stem-like cell expansion and resistance to anticancer treatment such as cisplatin (50 lM) or taxol (500 nM), or by ionizing radiation (10 Gy) in both glioma cell lines (U87, U373) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…For example, ionizing radiation has been reported to elicit such responses and overexpressed iNOS/NO has been implicated (76), but the underlying regulation of iNOS expression were not investigated. Of related interest is a recent study demonstrating that JQ1 can function as a radiosensitizer, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ionizing radiation has been reported to elicit such responses and overexpressed iNOS/NO has been implicated (76), but the underlying regulation of iNOS expression were not investigated. Of related interest is a recent study demonstrating that JQ1 can function as a radiosensitizer, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exploiting iNOS/NO for proliferative signaling, glioblastoma cells are known to rely on NO for migratory and invasive potency (26,(42)(43)(44). We compared the effects of 1400W and JQ1 on surviving U87 cell invasiveness after a typical ALA/light challenge.…”
Section: Jq1 Suppression Of Inos/no Anti-pdt Effectsmentioning
confidence: 99%
“…glioblastoma cells preferentially activate the signaling components that are involved in DNA damage checkpoint and thereby repair IR-induced DNA damage more efficiently than CD133-glioblastoma cells. However, previously, Kim et al observed an increase of cancer stem cell population to a greater extent by fractionated radiation than a single high dose of radiation (Kim et al 2013a). Since a higher single dose of radiation is predicted to be more powerful for selection of cancer stem cells than fractionated radiation, it is hard to explain this phenomena with the selection hypothesis.…”
Section: Radiation-enhanced Cancer Stem Cellsmentioning
confidence: 89%
“…The percentage of CD133-expressing cells as analyzed by FACS also correlated with the rate of tumor formation when implanted in mice. Likewise, Kim et al reported that treatment of glioblastoma cells with radiation stimulates expansion of glioma stem cells through nitric oxide (NO) production mediated by inducible NO synthase (iNOS) (Kim et al 2013a). They demonstrated that treatment with either single radiation (6 Gy) or fractionated radiation (2 Gy x3) resulted in the increase of CD133?…”
Section: Radiation-enhanced Cancer Stem Cellsmentioning
confidence: 99%
“…However, only associate with an increased risk of radiation is not possible, as these specialists have had contact with other possibly carcinogenic factors, such as, for example, arsenic, chemotherapy, etc. Negative results were obtained by observing a cohort of radiologists in China and employees of nuclear facilities of US and UK (Kim et al, 2013). Based on a number of epidemiological studies can be concluded that occupational exposure to ionizing radiation does not increase the risk of brain tumors.…”
Section: Discussionmentioning
confidence: 99%